Design and Implementation Intelligent Adaptive Front-lighting System of Automobile using Digital Technology on Arduino Board - H. Dahou; R. El Gouri; Mohammed Alareqi; K. Mateur; A. Mezouari; A. Zemmouri; L. Hlou (Institute of Advanced Engineering and Science, 2018)
The automatic light AFS (Adaptive Front - Lighting System) is added to the capabilities of modern vehicles that will improve the safety of vehicle drivers and passengers traveling at night. A new architecture of the AFS has proposed in this paper. This architecture is powerful and intelligent using the PWM technique on ARDUINO Board replaces the old mechanical system based on stepper motors.